Unlocking Speaking Potential: The Power of the Problem Posing Approach - Rina Asrini Bakri; Saiful; M. Tahir; Amra Ariyani; Andi Haeriati Alimuddin; Sumirna (Eduvelop: Journal of English Education and Development, 2025)
The research explores about Problem Posing Approach in enhancing speaking skill at the second grade students at SMP Negeri 3 Mare in 2024/2025 academic year. Utilizing a pre experimental design featuring a single group with both pretest and posttest phases, the study focused on a population of 120 students distributed across four classes: 2A, 2B, 2C, and 2D. Through purposive sampling, class 2B was selected as the sample group, as most of its students were identified as having lower speaking proficiency. Initially, participants underwent an oral assessment to gauge their baseline speaking skills. This was followed by six instructional sessions applying the Problem Posing Approach, after which a post-test was administered. Speaking performance was assessed using several key indicators such as fluency, word choice, articulation, and overall clarity. The results indicated a notable enhancement in average performance scores, which increased from a mean score of 6.87 (SD = 0.71) before the intervention to 10.77 (SD = 0.62) afterward. A paired-sample t-test confirmed the statistical significance of this increase at the 0.05 level (t = 21.06; df = 29; critical t = 2.045). These results suggest that incorporating learner-formulated questions into classroom practice significantly enhances classroom dialogue, improves language production, and strengthens student confidence in speaking. The study concludes that the Problem Posing Approach is an effective pedagogical strategy for elevating speaking proficiency in EFL contexts where student participation is traditionally limited. Educators are encouraged to integrate structured problem formulation and peer dialogue into speaking curricula to cultivate both communicative competence and critical thinking.